Walking with a Mobile Phone: A Randomised Controlled Trial of Effects on Mood - Collin, Randi; Broadbent, Elizabeth (Psych, 2023)
It is now common to see pedestrians looking at their mobile phones while they are walking. Looking at a mobile phone can cause stooped posture, slower gait, and lack of attention to surroundings. Because these walking characteristics have been associated with negative affect, walking while looking at a mobile phone may have negative effects on mood. This study aimed to investigate whether walking while looking at a mobile phone had psychological effects. One hundred and twenty-five adults were randomised to walk in a park either with or without reading text on a mobile phone. Participants wore a fitness tracker to record pace and heart rate, and posture was calculated from video. Self-reported mood, affect, feelings of power, comfort, and connectedness with nature were assessed. The phone group walked significantly slower, with a more stooped posture, slower heart rate, and felt less comfortable than the phone-free group. The phone group experienced significant decreases in positive mood, affect, power, and connectedness with nature, as well as increases in negative mood, whereas the phone-free group experienced the opposite. There was no significant mediation effect of posture on mood; however, feeling connected with nature significantly mediated the effects of phone walking on mood. In conclusion, individuals experience better wellbeing when they pay attention to the environment rather than their phone while walking. More research is needed to investigate the effects of performing other activities on a mobile phone on mood while walking and in other settings.